Study on interlocking concrete block pavement (ICBP) made with clamshell. - Mohd Aizuddin Yusri (School of Environmental Engineering, University Malaysia Perlis, 2012)
At present, the construction sector is important for developed countries. Today, this sector has grown rapidly in Malaysia. Therefore, the raw materials to be used in this sector will be reduced and this will be a problem for the country. To solve this problem, the research should be conducted from time to time to reduce the consumption of raw materials in industry, in addition to being cost effective, for example the use of materials such as clamshells. These clamshells are source widely available and very cheap because it is a waste. Modification of Concrete Block Pavement (ICBP) using shells instead of sand has been investigated in this research. The main aim of this research is to study the physical and engineering properties of modified (ICBP) blocks using clamshell including compression test and water absorption. Both properties of the modified (ICBP) blocks will be comparing with the control (ICBP) blocks. The chemical composition of clamshell also been identify. The ratio of the (ICBP) blocks use in this research is 1:3 which stand for 1 part cement, 3 parts sand and the clamshell are used as part of sand replacement in the mix with percentage of 10%, 20%, 30%, 40%, and 50% proportion of clamshell. Optimum percentage obtained from this study is 30%.